How to attract mega sports events to Lisbon? - Reis, Catarina Martins (2018)
Lisbon is an ancient city filled with history, culture, diversity and a life of its own. Sports are one of the key focus areas, as part of the city’s development plan. Is within this context that a study to support Lisbon’s application to become the European Capital of Sports 2021 was conducted. The purpose of this thesis is to underline the main success factors to attract mega-events to our city, satisfying the main group of stakeholders. To understand the key factors involved, not only literature research was conducted but also an empirical one to add and to develop the proposed ideas. A focus group with representatives from the three main groups involved was conducted: Sport Events Organizers, Sponsors and Public Authorities. The purpose of this discussion was to identify the critical success factors to attract mega sport events, which factors motivate the groups to participate, and what are the ones that may compromise their participation. Furthermore, it could also be identified the factors that the city must improve to be a trustworthy applicant and complete host. Findings suggest that Lisbon is a city with a hosting profile, demonstrating capability in many of the crucial areas, some solid points and some improvement areas.